Does perfectionism in leaders increase or impede team decision-making performance? Team level LMX as a key factor. (October 2022) - Song, Shanghao; Chen, Xiaoxuan; Wang, Wenzhou; Bai, Shuyuan; Xu, Xinfeng; Zhang, Yiyuan
Abstract: Based on leader-member exchange (LMX) theory and the social exchange perspective, the study investigates the association between leader perfectionism and team decision-making performance and tests the moderating effect of team members' task performance. By adding team level LMX (TLMX) as a mediator, we construct a moderated mediation model. Data were gathered from a multisource and multiphase survey of Chinese organizations. The results indicate that leader perfectionism has a negative, indirect effect on team decision-making performance via TLMX. As a boundary condition, team members' task performance can moderate this mediated relationship. Specifically, the lower team members' task performance is, the lower TLMX and team decision-making performance is. Unexpectedly, when TLMX is controlled for, leader perfectionism has a positive and direct effect on team decision-making performance.